Vi skal passe på os selv: En diskursanalytisk undersøgelse af Sundhedsstyrelsens italesættelse af patienters selvmonitorering - Kappelgaard, Lisbeth (Academic Quarter | Akademisk kvarter, 2015)
Self-monitoring is increasingly used as part of treatment and prevention in the Danish healthcare system. An example may be the chronically ill individual who measures different physical fluctuations in the body, or it may be citizens with depression history who monitor their energy level or mood to increase their own awareness of a possible relapse. The technological opportunity for self-monitoring is often articulated as patient-caring – as ways individuals can help themselves. With theoretical and methodological inspiration from discourse theory, the objective of this article is to illustrate the articulations, hegemonic positions and rationales, which construct self-monitoring as self-caring.